(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In the era of digital transformation, managerial staff must continuously develop their digital competence to ensure effective leadership and decision-making. This study examines the need for improved software solutions to enhance the digital competence of managerial personnel in Uzbekistan. The paper explores the latest trends in digital education, analyzes the challenges faced by managers in acquiring digital skills, and proposes an optimized software solution tailored to their professional needs. The findings suggest that an integrated, user-friendly software system can significantly contribute to the digital competence development of managerial staff, improving organizational efficiency and innovation, particularly within the context of Uzbekistan’s digitalization initiatives.